R-Shiny as an interface for Data Visualization and Data Analysis on the Brazilian Digital Library of Thesis and Dissertations (BDTD) - (:unkn) unknown (Universität Hamburg, 2019)
This work presents a use case of building a data visualization interface for open access repositories. The case of analysis is the Brazilian Digital Library of Thesis and Dissertations (BDTD). ​R is a statistical tool very used among developers and programmers. One of its packages is called ​Shiny​, that makes it easy to build interactive web apps straight from ​R.​ Through the app, the user can visualize data in a fast and customizable way. It could help them to keep track of metadata and usage statistics over the institutional repositories and can also be applied to discovering scientific information, such as bibliographic references and lists of specialists in certain research domain. These data visualization tools can stimulate others to create open repositories and join either national, regional or international repositories networks.
R-Shiny como interface para Visualização de Dados e Análise de Dados na Biblioteca Digital Brasileira de Teses e Dissertações (BDTD)
Keywords: BDTD; Open Repositories; Data analysis; Data visualization; R; R-Shiny; Modelos analíticos e de simulação